Localization of competence-induced proteins in Streptococcus pneumoniae. - Vijayakumar, M N (1986)
Intracellular locations of 11 proteins associated with the development of competence in Streptococcus pneumoniae were examined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis of subcellular fractions prepared from protoplasts. Controls showed that the competence-induced proteins were stable during the formation of protoplasts at 25 degrees C even though some had a half-life of only 8 min at 37 degrees C. Five competence-induced proteins p38, p27, p19.5, p16, and p14.5, were found in the cytoplasm. Two, p52 and p41, were associated with the membrane, and one, p10, was extracellular. Three others, p50, p36, and p29, were recovered in both cytoplasmic and membrane fractions. No competence-induced protein was detected in the periplasmic fraction except under conditions where leakage of all components was occurring, a phenomenon that was seen in many preparations. Similar fractionation of competent cells soon after uptake of [3H]DNA showed the "eclipse complex" of single-stranded DNA and p19.5 was associated approximately one-third with membranes and two-thirds with cytoplasmic fractions, with almost none in the periplasm. This result suggests strongly that at the time the donor DNA entered the cytosol it was in single-stranded form and it had not yet paired with the recipient DNA.